Penerapan Metode AHP Dalam Menentukan Set Top Box TV Terbaik - Ratih Adinda Destari; Asbon Hendra Azhar (LPPM STIKOM Tunas Bangsa, 2024)
The use of TV Set Top Boxes currently in Indonesia is increasing greatly and is being used by the public. Currently, people can continue to enjoy digital broadcasts without having to change analog television to digital by using a device called a set-top box. This decoder is useful for converting or replacing digital signals into images and sound that can be displayed on ordinary analog TVs which are widely used by the public. Various brands of set-top boxes are sold by the Company with different specifications and prices. Where people will find it very difficult to determine the best choice due to a lack of understanding about this TV Set Top Box. From the problems that occur, a decision support system is needed to help people choose a TV Set Top Box according to the needs that exist in the community. The criteria used in this research are price, resolution, EWS (Early Warning System) features, guarantees, certificates and promotions. This Set-Box selection decision support system uses the Analytical Hierarchy Process (AHP) method. This method is used because it can provide the best decision based on the highest value to the lowest value. The result of this research is a decision support system that can provide recommendations for selecting the best decoder for digital TV broadcasts based on the highest to lowest values using the AHP method. From the calculation results, it was found that POLYTRON PDV 600T2 had a value of 0.2466, MATRIX APPLE had a value of 0.2327, EVENIX H1 had a value of 0.2452 and LUBY DVB T2 0,2756